Perfluorophenyl Derivatives as Unsymmetrical Linkers for Solid Phase Conjugation - Alapour, Saba; Sharma, Anamika; de la Torre, Beatriz G.; Ramjugernath, Deresh; Koorbanally, Neil A.; Albericio, Fernando (Frontiers in Chemistry, 2018)
Linkers play major roles in conjugation chemistry towards the advancement of drug discovery. Two different series of fluorinated linkers were introduced to the backbone of a model peptide using solid phase peptide synthesis. These fluorinated linkers have the potential to conjugate two asymmetrical groups. This has not been done using other fluorinated linkers. This study deals with application of linkers with S, N and O terminals and reports on the investigation of their chemoselectivity and activity for branching peptide backbones using a chosen model peptide. These fluorinated linkers have unique properties that will make it possible for a large diversity of bioconjugated chemicals for different bioapplications to be designed and synthesised